OpticalTrust: A Sensor-to-Blockchain Framework Using Free-Space Optical Communication - Parveen Bajaj; Aman Kataria; Vikram Puri; Sachin Gupta; Hong Min (Sensors)
In the dynamic landscape of the tech industry, the escalating requirement for swift and secure data transmission has catalyzed innovation in integrated communication systems. Free-Space Optics (FSOs) has emerged as a promising contender in optical communications. While conventional optical fiber systems can achieve bit rates of up to 40 Gbps with proper design, they are limited primarily by electronics rather than semiconductor laser capabilities. This study presents an integrated framework that combines FSOs, blockchain technology, and sensor networks to address challenges in data transmission, security, and environmental adaptation. This study analyzes FSOs system performance through the Quality (Q) Factor and Bit Error Rate (BER), comparing systems with and without Erbium-Doped Fiber Amplifiers (EDFAs) across various bit rates (8, 12, 16, and 20 Gbps) and transmission distances (5–25 km). To enhance data security and reliability, a blockchain architecture is incorporated with smart contracts and an InterPlanetary File System (IPFS) for storing and validating results generated from FSOs simulation. Additionally, this study explores the design of sensor network models for FSOs technology by investigating how distributed sensor arrays can be theoretically integrated with FSOs systems, with testing focused on FSOs performance and blockchain implementation.